The Impact of Introducing Charter Schools on Teachers' Instruction in the UAE Education Sector- A Case Study in Charter Schools in Abu Dhabi - DABOUS, SAMER (2024)
Abstract The dissertation explores the impact of charter schools on teaching practices in Abu Dhabi, of the United Arabe Emirates, by utilizing a mixed-method investigation that aims to offer insights into the autonomy of teachers and their instruction strategies. The study involved 55 teachers through quantitive surveys, and 5 teachers through qualitative interviews, to close the gap in existing literature concerning charter schools in the United Arab Emirates. It was concluded through quantitative research that teachers in charter schools have a high level of autonomy at 847%, who express their satisfaction concerning their capacity to select instructional strategies and manage classroom activities. Through qualitative analysis, teachers praised the innovative environment that was created by the management organization but voiced their concerns over workload. The findings highlight the significance of striking a balance between suitable support systems and autonomy to improve instructional quality and teacher job satisfaction. This study contributes to the discourse on educational reforms by highlighting the necessity for policies that support teacher autonomy and growth within the charter school framework.